Nine-layer co-extruded high temperature resistant film containing polyethylene and nylon, preparation method and application in carbon fiber autoclave molding process

By developing a nine-layer coextruded high-temperature resistant film containing polyethylene and nylon, using composite materials of epoxy-based cage-type silicone quaternary ammonium salt capping agent and Elosite nanotubes, the existing high-temperature membrane cost is solved and the cost and The problem of poor environmental adaptability has achieved high temperature stability and cost-effectiveness above 200℃, and is suitable for carbon fiber hot pressing tank forming process.

CN118909453BActive Publication Date: 2024-12-20SUZHOU ZIJIN PLASTIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411414677.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-20
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

In the existing hot press tank molding process, high-temperature deformable diaphragm materials such as polyimide films and rubber films are costly and are not suitable for large-scale production, and their performance is affected in low-temperature and high-temperature environments, making it difficult to meet high-temperature durability and cost-effectiveness. demand.

Method used

A nine-layer coextruded high-temperature resistant film containing polyethylene and nylon was developed to prepare epoxy-based cage silicone quaternary ammonium capping agent and bis(epoxy) cage silicone quaternary ammonium salt cross-link The agent modified the nylon resin, combined with Elostone nanotubes, and used nine-layer coextrusion blow molding process to prepare a hot insulation film for carbon fiber hot pressing tank molding process.

Benefits of technology

The nine-layer coextruded high-temperature resistant film prepared does not deform or decompose at high temperatures of 200°C or above. It is suitable as a diaphragm for the carbon fiber hot pressing tank molding process, significantly improves high-temperature resistance, reduces production costs, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118909453B_ABST
    Figure CN118909453B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of diaphragms for carbon fiber autoclave forming process, and discloses a nine-layer co-extruded high-temperature resistant film containing polyethylene and nylon materials, a preparation method and an application of the film in the carbon fiber autoclave forming process. A nylon resin is modified by synthesizing and using an epoxy cage-type organosilicon quaternary ammonium salt end-capping agent or / and a di(epoxy) cage-type organosilicon quaternary ammonium salt cross-linking agent to perform end-capping and / or cross-linking treatment, and then the amide functional groups rich in the main chain of the nylon resin and the hydroxyl functional groups rich in the surface of the halloysite nanotube are compounded through hydrogen bonding to obtain a high-temperature resistant nylon composite material; the high-temperature resistant nylon composite material is used as a raw material for an intermediate high-temperature resistant functional layer, and a nine-layer co-extruded blow molding film-forming process is adopted to prepare the nine-layer co-extruded high-temperature resistant film, which can withstand a high temperature of 200°C or above, does not deform or decompose, and is suitable for use as a diaphragm in a hot diaphragm forming process of the carbon fiber autoclave forming process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of diaphragms for carbon fiber autoclave molding processes, and specifically to a nine-layer co-extruded high-temperature resistant film containing polyethylene and nylon materials, a preparation method, and an application in carbon fiber autoclave molding processes. Background Art

[0002] The autoclave molding process is the main manufacturing method for carbon fiber reinforced resin-based composite materials. Generally, the prepreg is made into a flat plate by automatic tape laying technology, and then the prepreg flat plate is formed by the hot diaphragm molding process. Finally, the formed prepreg is placed in the autoclave for curing and molding. In the hot diaphragm molding process, the flat plate stack is placed between two freely deformable diaphragms, and the diaphragms are clamped at the edge of the mold. First, the double diaphragms are evacuated to provide a pressure to support the flat plate stack, and the flat plate stack and the diaphragm are assembled on the vacuum box. Then, infrared heating is performed on the flat plate stack. When the process temperature is reached, the vacuum box is evacuated. The flat plate stack between the two diaphragms will slowly fit to the mold surface under pressure. The diaphragm is usually a high-temperature deformable material, such as a polyimide film or a rubber film. During the molding process, the diaphragm clamped at the edge of the vacuum box is in a stretched state, so there is mutual friction between the film and the flat plate stack, which helps to keep the flat plate stack in tension, thereby preventing the fiber from buckling and wrinkling during the molding process. When the molding process is completed, the part is cooled under atmospheric pressure to below the softening temperature of the prepreg, and finally the pressure is released and the diaphragm is peeled off from the mold to take out the part.

[0003] Polyimide film has good high temperature resistance and is suitable for applications in high temperature environments, but its production cost is high and the production difficulty is greater, making it unsuitable for large-scale production.

[0004] Rubber film has good elasticity and wear resistance, while its disadvantages mainly include high cost and unsuitability for all environmental conditions. For example, it may become hard at low temperatures and too soft at high temperatures, affecting its performance. Summary of the invention

[0005] The present invention independently develops and prepares a nine-layer co-extruded high-temperature resistant film containing polyethylene and nylon materials. The nine-layer co-extruded high-temperature resistant film can be used as a diaphragm in a hot diaphragm forming process in a carbon fiber autoclave forming process.

[0006] A method for preparing a nine-layer co-extruded high-temperature resistant film containing polyethylene and nylon materials, comprising the following steps:

[0007] Step 1, preparing a high temperature resistant modifying agent for nylon resin, wherein the high temperature resistant modifying agent is an epoxy cage type organosilicon quaternary ammonium salt end-capping agent or / and a di(epoxy) cage type organosilicon quaternary ammonium salt cross-linking agent;

[0008] Step 2, using the epoxy functional group of the epoxy cage type organosilicon quaternary ammonium salt end-capping agent and / or the epoxy functional group of the di(epoxy) cage type organosilicon quaternary ammonium salt cross-linking agent to react with the terminal amino functional group or the terminal carboxyl functional group on the main chain of the nylon resin to complete the end-capping and / or cross-linking modification of the nylon resin;

[0009] Then, the amide functional groups rich in the main chain of the nylon resin and the hydroxyl functional groups rich in the surface of the halloysite nanotubes are compounded through hydrogen bonding to prepare a high-temperature resistant nylon composite material;

[0010] The amount of halloysite nanotubes used is 5-15wt% of the nylon resin;

[0011] The amount of epoxy cage-type silicone quaternary ammonium salt capping agent is 0-8wt% of the nylon resin;

[0012] The amount of di(epoxy) cage-type organosilicon quaternary ammonium salt crosslinking agent is 0~8wt% of the nylon resin;

[0013] Step three, using high temperature resistant nylon composite material as the raw material of the middle high temperature resistant functional layer, polyethylene resin as the raw material of the protective layer, maleic anhydride grafted polyethylene resin as the raw material of the bonding layer, and adopting a nine-layer co-extrusion blow molding film forming process to prepare a nine-layer co-extruded high temperature resistant film containing polyethylene and nylon materials.

[0014] Preferably, the preparation method of the epoxy cage-type organosilicon quaternary ammonium salt capping agent is:

[0015] Tertiary amino heptadiphenyl cage polysilsesquioxane monomer was synthesized by the vertex-capping method using trisilanol heptadiphenyl cage polysilsesquioxane as raw material and (N,N-dimethyl-3-aminopropyl)trimethoxysilane as capping agent.

[0016] By utilizing the nucleophilic substitution reaction mechanism, the tertiary amine functional group of the nucleophilic reagent tertiary amino heptadiphenyl cage-type polysilsesquioxane monomer undergoes a quaternization reaction with the chlorine functional group of epichlorohydrin to generate an epoxy cage-type organosilicon quaternary ammonium salt capping agent.

[0017] Preferably, the preparation method of the di(epoxy) cage-type organosilicon quaternary ammonium salt cross-linking agent is:

[0018] Phenyltrimethoxysilane was used as raw material, and the hydrolysis-condensation method was adopted. The hydrolysis-condensation reaction of phenyltrimethoxysilane was catalyzed by sodium hydroxide. 3-dimethylaminopropyl (dimethoxy)methylsilane was used as a capping agent. Di(tertiary amino) octaphenyl cage-type polysilsesquioxane monomer was synthesized by the vertex-capping method under the catalysis of triethylamine.

[0019] By utilizing the nucleophilic substitution reaction mechanism, the tertiary amine functional group of the nucleophilic reagent di(tertiary amino) octaphenyl cage-type polysilsesquioxane monomer undergoes a quaternization reaction with the chlorine functional group of epichlorohydrin to generate a di(epoxy) cage-type organosilicon quaternary ammonium salt crosslinking agent.

[0020] Preferably, the preparation method of the nine-layer co-extruded high temperature resistant film containing polyethylene and nylon materials is:

[0021] Step 1: Design the film structure of the nine-layer co-extruded high temperature resistant film and determine the raw materials and dosage of each film layer, as follows:

[0022] The first polyethylene layer: the raw material is low-density polyethylene resin, the dosage is 5~15wt%;

[0023] Second polyethylene layer: the raw material is high-density polyethylene resin, the dosage is 5~15wt%;

[0024] The third polyethylene layer: the raw material is low-density polyethylene resin, the dosage is 5~15wt%;

[0025] The first bonding layer: the raw material is maleic anhydride grafted polyethylene resin, the dosage is 3~8wt%;

[0026] Nylon layer: the raw material is high temperature resistant nylon composite material, the dosage is 20~40wt%;

[0027] Second bonding layer: the raw material is maleic anhydride grafted polyethylene resin, the dosage is 3~8wt%;

[0028] The fourth polyethylene layer: the raw material is low-density polyethylene resin, the dosage is 5~15wt%;

[0029] The fifth polyethylene layer: the raw material is high-density polyethylene resin, the dosage is 5~15wt%;

[0030] The sixth polyethylene layer: the raw material is low-density polyethylene resin, the dosage is 5~15wt%;

[0031] Step 2: Using a nine-layer co-extrusion film blowing unit, and controlling the blowing ratio at 2.5-2.9, a nine-layer co-extruded high temperature resistant film is prepared.

[0032] Preferably, the plasticizing extrusion process parameters of the nylon layer are as follows: the temperatures of zones 1-3 are 240-260°C, 270-290°C, and 310-330°C, respectively; the flow channel temperature is 310-320°C; and the rotation speed is 50-70 r / min.

[0033] The thickness of the nine-layer co-extruded high-temperature resistant film containing polyethylene and nylon prepared according to the above method is 50-150 μm.

[0034] The heat deformation temperature of the nine-layer co-extruded high-temperature resistant film containing polyethylene and nylon prepared according to the above method is greater than 200°C.

[0035] Compared with the prior art, the present invention has the following beneficial technical effects:

[0036] The invention synthesizes two modification reagents with high temperature resistance function (epoxy cage type organosilicon quaternary ammonium salt end-capping agent and di(epoxy) cage type organosilicon quaternary ammonium salt cross-linking agent), uses the epoxy cage type organosilicon quaternary ammonium salt end-capping agent and / or the di(epoxy) cage type organosilicon quaternary ammonium salt cross-linking agent to perform modification treatment on nylon resin, and then the amide functional groups rich in the main chain of the molecule in the nylon resin and the hydroxyl functional groups rich in the surface of the halloysite nanotube are compounded through hydrogen bonding to obtain a high temperature resistant nylon composite material;

[0037] A nine-layer co-extruded high-temperature resistant film is prepared by using high-temperature resistant nylon composite material as the raw material for the middle high-temperature resistant functional layer of the nine-layer co-extruded film and polyethylene as the raw material for the protective layer of the nine-layer co-extruded film. The film can withstand high temperatures of 200°C and above without deformation or decomposition, and is suitable for use as a diaphragm in the hot diaphragm molding process of the carbon fiber autoclave molding process. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 These are the performance test results of the nine-layer co-extruded high temperature resistant film. DETAILED DESCRIPTION

[0039] The main raw materials used in the present invention are as follows:

[0040] The nylon resin is nylon 66 resin purchased from Tianjin Lairui Plastic Sales Co., Ltd., and its brand is FG170;

[0041] Low-density polyethylene resin was purchased from Jiangsu Rantai Plastics Co., Ltd., and its brand is LD 150DW;

[0042] High-density polyethylene resin was purchased from Dongguan Longhuang Plastic Raw Materials Co., Ltd., and its brand number is FB5600;

[0043] Maleic anhydride grafted polyethylene resin was purchased from Dongguan Taotao Plastic Raw Materials Co., Ltd., with the brand number 4288;

[0044] Halloysite nanotubes were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. and had a diameter of 100-150 nm and a length of 3-5 μm.

[0045] Experimental Example 1:

[0046] The epoxy cage-type organosilicon quaternary ammonium salt capping agent is prepared, and the preparation process is as follows:

[0047] Synthesis of tertiary amino heptaphenyl cage polysilsesquioxane monomer: trisilanol heptaphenyl cage polysilsesquioxane was used as raw material, (N,N-dimethyl-3-aminopropyl) trimethoxysilane was used as capping agent, and tertiary amino heptaphenyl cage polysilsesquioxane monomer was synthesized by the vertex-capping method. The specific experimental steps were as follows: under nitrogen protection, 4.7g trisilanol heptaphenyl cage polysilsesquioxane and 50mL anhydrous tetrahydrofuran were added to a three-necked flask, stirred at room temperature until completely dissolved, placed in an ice-water bath and stirred for 15min, and then 1.1mL (N,N-dimethyl-3-aminopropyl) trimethoxysilane was added dropwise to the three-necked flask, and continued to stir in the ice-water bath for 5min, and then stirred at room temperature for 5 days, and then methanol and acetonitrile were used for precipitation, filtration, washing, and vacuum drying at 50°C for 8h to obtain a tertiary amino heptaphenyl cage polysilsesquioxane monomer, whose chemical structure is:

[0048] ;

[0049] Synthesis of epoxy cage-type organosilicon quaternary ammonium salt capping agent: Utilizing the nucleophilic substitution reaction mechanism, the tertiary amine functional group of the nucleophilic reagent tertiary amino heptaphenyl cage-type polysilsesquioxane monomer and the chlorine functional group of epichlorohydrin undergo quaternization reaction to generate an epoxy cage-type organosilicon quaternary ammonium salt capping agent. The specific experimental steps are as follows: under the protection of nitrogen, 5.2g of tertiary amino heptaphenyl cage-type polysilsesquioxane monomer, 1.0mL of epichlorohydrin and 50mL of anhydrous tetrahydrofuran are added to a three-necked flask, the temperature is raised to 40°C for reaction for 12h, the excess epichlorohydrin is removed by reduced pressure distillation, the mixture is washed with ether, and vacuum dried at 40°C for 12h to obtain an epoxy cage-type organosilicon quaternary ammonium salt capping agent, the chemical structure of which is:

[0050] ;

[0051] The hydrogen nuclear magnetic resonance spectrum of the epoxy cage-type organosilicon quaternary ammonium salt capping agent is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.89-0.93 (t, 2H), 1.74-1.81 (m, 2H), 3.28 (s, 6H), 3.42-3.46 (t, 2H), 3.53-3.55 (d, 2H), 3.67-3.81 (m, 2H), 4.01-4.08 (m, 1H), 7.33-7.54 (m, 35H).

[0052] Experimental Example 2:

[0053] Preparation of di(epoxy) cage-type organosilicon quaternary ammonium salt crosslinking agent, the preparation process is as follows:

[0054] Synthesis of di(tertiary amino) octaphenyl cage-type polysilsesquioxane monomer: firstly, phenyltrimethoxysilane was used as raw material, and the hydrolysis-condensation method was adopted to catalyze the hydrolysis and polycondensation reaction of phenyltrimethoxysilane with sodium hydroxide, and then 3-dimethylaminopropyl (dimethoxy)methylsilane was used as a capping agent, and the di(tertiary amino) octaphenyl cage-type polysilsesquioxane monomer was synthesized by the vertex-capping method under the catalysis of triethylamine. The specific experimental steps are as follows: under the protection of nitrogen, 19.8g of phenyltrimethoxysilane, 2.7g of sodium hydroxide, 100mL of isopropanol and 10mL of deionized water were added to a three-necked flask, and the temperature was raised to 4 The mixture was stirred at 0°C until completely dissolved, and then heated to 90°C and stirred under reflux for 4 hours. After cooling to room temperature, the mixture was stirred for 12 hours, filtered, washed repeatedly with isopropanol, dried, and added to a three-necked flask with 1.8 mL of triethylamine and 100 mL of tetrahydrofuran. The mixture was stirred and dissolved under ice bath conditions for 2 hours. Then, 5.4 mL of 3-dimethylaminopropyl (dimethoxy)methylsilane was slowly added dropwise to the three-necked flask, the ice bath was removed, and the mixture was stirred at room temperature for 24 hours. The solvent was removed by rotary evaporation, washed repeatedly with methanol, and dried under vacuum at 50°C for 8 hours to obtain a di(tertiary amino)octaphenyl cage-type polysilsesquioxane monomer having the chemical structure:

[0055] ;

[0056] Synthesis of di(epoxy) cage-type organosilicon quaternary ammonium salt crosslinking agent: Utilizing the nucleophilic substitution reaction mechanism, the tertiary amine functional group of the nucleophilic reagent di(tertiary amino) octaphenyl cage-type polysilsesquioxane monomer and the chlorine functional group of epichlorohydrin undergo quaternization reaction to generate a di(epoxy) cage-type organosilicon quaternary ammonium salt crosslinking agent. The specific experimental steps are as follows: under the protection of nitrogen, 6.6 g of di(tertiary amino) octaphenyl cage-type polysilsesquioxane monomer, 2.0 mL of epichlorohydrin and 80 mL of anhydrous tetrahydrofuran are added to a three-necked flask, the temperature is raised to 40°C for reaction for 15 hours, the excess epichlorohydrin is removed by reduced pressure distillation, the agent is washed with ether, and vacuum dried at 40°C for 12 hours to obtain a di(epoxy) cage-type organosilicon quaternary ammonium salt crosslinking agent, the chemical structure of which is:

[0057] ;

[0058] The nuclear magnetic resonance hydrogen spectrum of the di(epoxy) cage-type organosilicon quaternary ammonium salt crosslinker is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.09 (s, 6H), 1.14-1.18 (t, 4H), 1.67-1.74 (m, 4H), 3.29 (s, 12H), 3.43-3.47 (t, 4H), 3.56-3.57(d, 4H), 3.67-3.81(m, 4H), 4.01-4.08(m, 2H), 7.33-7.54(m, 40H). Embodiment 1:

[0059] Preparation of high temperature resistant nylon PA-Ⅰ: The epoxy functional group of the epoxy cage type silicone quaternary ammonium salt capping agent reacts with the terminal amino functional group or terminal carboxyl functional group on the main chain of the nylon 66 resin to complete the end-capping modification of the nylon 66 resin by the epoxy cage type silicone quaternary ammonium salt capping agent. Then, the amide functional group rich in the main chain of the nylon 66 resin and the hydroxyl functional group rich in the surface of the halloysite nanotube are compounded through hydrogen bonding to obtain the high temperature resistant nylon PA-Ⅰ. The specific experimental steps are as follows: 40 mL of anhydrous tetrahydrofuran and 60 mL of anhydrous N,N -dimethylformamide was added to a three-necked flask, the temperature was raised to 60°C, 10g of nylon 66 resin was added and stirred until all dissolved, 10mL of anhydrous tetrahydrofuran solution containing 0.6g of epoxy cage-type organosilicon quaternary ammonium salt capping agent was slowly added to the three-necked flask under nitrogen protection, the temperature was raised to 80°C and stirred for 6h, the temperature was lowered to 40°C, 10mL of anhydrous tetrahydrofuran solution containing 1.0g of halloysite nanotubes was slowly added to the three-necked flask, the temperature was maintained at 40°C and stirred for 6h, the solvent was removed by rotary evaporation, and the high temperature resistant nylon PA-Ⅰ was obtained;

[0060] Preparation of high temperature resistant nylon PA-Ⅱ: The epoxy functional group of the di(epoxy) caged organosilicon quaternary ammonium salt crosslinker reacts with the terminal amino functional group or terminal carboxyl functional group on the main chain of the nylon 66 resin to complete the crosslinking modification of the nylon 66 resin by the di(epoxy) caged organosilicon quaternary ammonium salt crosslinker, and then the amide functional group rich in the main chain of the nylon 66 resin and the hydroxyl functional group rich in the surface of the halloysite nanotube are compounded through hydrogen bonding to obtain the high temperature resistant nylon PA-Ⅱ. The specific experimental steps are different from those of the high temperature resistant nylon PA-Ⅰ only in that the epoxy caged organosilicon quaternary ammonium salt end-capping agent is replaced by the di(epoxy) caged organosilicon quaternary ammonium salt crosslinker;

[0061] Preparation of high temperature resistant nylon PA-Ⅲ: firstly, nylon 66 resin is modified by using epoxy cage type silicone quaternary ammonium salt capping agent and di(epoxy) cage type silicone quaternary ammonium salt crosslinking agent, and then the amide functional groups rich in the main chain of the nylon 66 resin and the hydroxyl functional groups rich in the surface of the halloysite nanotubes are compounded through hydrogen bonding to obtain high temperature resistant nylon PA-Ⅲ. The specific experimental steps are different from those of high temperature resistant nylon PA-Ⅰ only in that 0.6g of epoxy cage type silicone quaternary ammonium salt capping agent is replaced by 0.3g of epoxy cage type silicone quaternary ammonium salt capping agent and 0.3g of di(epoxy) cage type silicone quaternary ammonium salt crosslinking agent. Embodiment 2:

[0062] Preparation of nine-layer co-extruded high-temperature resistant film: Design the film structure of the nine-layer co-extruded high-temperature resistant film, the raw materials of each film layer and the amount (the specific contents are shown in Table 1 below), use a nine-layer co-extruded film blow molding unit, and put the raw materials of each film layer into the hoppers of the nine screw extruders of the nine-layer co-extruded film blow molding unit respectively. The molten resin is converged at the head of the machine through a diverter, extruded through the die head, blown and pulled (the blowing ratio is controlled at 2.6), cooled, and wound to prepare a nine-layer co-extruded high-temperature resistant film with a thickness of 100 μm.

[0063] Table 1 Experimental formula and process parameters of nine-layer co-extruded high temperature resistant film

[0064]

[0065] When the high temperature resistant nylon composite material is high temperature resistant nylon PA-Ⅰ, the prepared product is recorded as nine-layer co-extruded high temperature resistant film Ⅰ;

[0066] When the high temperature resistant nylon composite material is high temperature resistant nylon PA-Ⅱ, the prepared product is recorded as nine-layer co-extruded high temperature resistant film Ⅱ;

[0067] When the high temperature resistant nylon composite material is high temperature resistant nylon PA-Ⅲ, the prepared product is recorded as nine-layer co-extruded high temperature resistant film III.

[0068] Comparative Example:

[0069] Preparation of nine-layer co-extruded film: Nylon 66 resin was used to replace the high-temperature resistant nylon in the nine-layer co-extruded high-temperature resistant film, and the nine-layer co-extruded film was prepared according to the same experimental steps and process conditions.

[0070] Performance Test:

[0071] 1. Mechanical properties test:

[0072] (1) Mechanical properties test at room temperature: According to GB / T 1040.1-2018 "Determination of tensile properties of plastics", a 150 mm × 20 mm sample was fixed on an Instron 5565 universal tensile testing machine at room temperature and a tensile test was performed at a tensile rate of 5 mm / min.

[0073] (2) High temperature mechanical properties test: According to GB / T 1040.1-2018 "Determination of tensile properties of plastics", a 150 mm × 20 mm sample was first placed in an oven at 200 °C for 48 h, and then fixed on an Instron 5565 universal tensile testing machine for tensile testing at a tensile rate of 5 mm / min.

[0074] 2. Heat deformation temperature test:

[0075] According to GB / T 1634-2004 "Determination of load deformation temperature of plastics", a sample of 80mm×10mm×4mm is placed on a support with a span of 64mm. After installation, it is immersed in silicone oil and a load is applied to the midpoint of the two supports. Under the condition of isothermal heating rate (120℃ / h), when the bending deformation of the sample under load reaches the preset value, the temperature at this time is the heat deformation temperature;

[0076] The conditions set in this experiment are: the highest temperature is 250℃; the starting temperature is 35℃; the cooling temperature is 35℃; the preheating time is 220s; the applied load is 8.0MPa; the end deflection condition is 0.34mm;

[0077] The above test results are shown in Table 2 and Figure 1 .

[0078] Table 2 Performance test results of nine-layer co-extruded high temperature resistant film

[0079]

[0080] By analyzing the performance test results, the following conclusions can be drawn:

[0081] The three nine-layer co-extruded high-temperature resistant films prepared by the present invention have achieved a beneficial technical effect of significantly improving the high-temperature resistant performance compared with the prior art;

[0082] Among them, the improvement effect of nine-layer co-extruded high temperature resistant film III is the most significant, while the improvement effects of nine-layer co-extruded high temperature resistant film I and nine-layer co-extruded high temperature resistant film II are not significantly different.

Claims

1. A method for preparing a nine-layer co-extruded high temperature resistant film containing polyethylene and nylon materials, It is characterized in that The steps include: Step 1, preparing a high temperature resistant modifying agent for nylon resin, wherein the high temperature resistant modifying agent is an epoxy cage type organosilicon quaternary ammonium salt end-capping agent or / and a di(epoxy) cage type organosilicon quaternary ammonium salt cross-linking agent; The chemical structural formula of the epoxy cage-type organosilicon quaternary ammonium salt capping agent is: ; The chemical structural formula of the di(epoxy) cage-type organosilicon quaternary ammonium salt cross-linking agent is: ; Step 2, using the epoxy functional group of the epoxy cage type organosilicon quaternary ammonium salt end-capping agent and / or the epoxy functional group of the di(epoxy) cage type organosilicon quaternary ammonium salt cross-linking agent to react with the terminal amino functional group or the terminal carboxyl functional group on the main chain of the nylon resin to complete the end-capping and / or cross-linking modification of the nylon resin; Then, the amide functional groups rich in the main chain of the nylon resin and the hydroxyl functional groups rich in the surface of the halloysite nanotubes are compounded through hydrogen bonding to prepare a high-temperature resistant nylon composite material; The amount of halloysite nanotubes used is 5-15wt% of the nylon resin; 10 parts by weight of nylon resin are modified by using 0.6 parts by weight of epoxy cage type organosilicon quaternary ammonium salt end-capping agent or 0.6 parts by weight of di(epoxy) cage type organosilicon quaternary ammonium salt cross-linking agent, or 10 parts by weight of nylon resin are modified by using 0.3 parts by weight of epoxy cage type organosilicon quaternary ammonium salt end-capping agent and 0.3 parts by weight of di(epoxy) cage type organosilicon quaternary ammonium salt cross-linking agent; Step three, using high temperature resistant nylon composite material as the raw material of the middle high temperature resistant functional layer, polyethylene resin as the raw material of the protective layer, maleic anhydride grafted polyethylene resin as the raw material of the bonding layer, and adopting a nine-layer co-extrusion blow molding film forming process to prepare a nine-layer co-extruded high temperature resistant film containing polyethylene and nylon materials.

2. A method for preparing a nine-layer co-extruded high temperature resistant film containing polyethylene and nylon according to claim 1, It is characterized in that The preparation method of the epoxy cage-type organosilicon quaternary ammonium salt capping agent is: Tertiary amino heptadiphenyl cage polysilsesquioxane monomer was synthesized by the vertex-capping method using trisilanol heptadiphenyl cage polysilsesquioxane as raw material and (N,N-dimethyl-3-aminopropyl)trimethoxysilane as capping agent. By utilizing the nucleophilic substitution reaction mechanism, the tertiary amine functional group of the nucleophilic reagent tertiary amino heptadiphenyl cage-type polysilsesquioxane monomer undergoes a quaternization reaction with the chlorine functional group of epichlorohydrin to generate an epoxy cage-type organosilicon quaternary ammonium salt capping agent.

3. A method for preparing a nine-layer co-extruded high temperature resistant film containing polyethylene and nylon according to claim 1, It is characterized in that The preparation method of the di(epoxy) cage-type organosilicon quaternary ammonium salt cross-linking agent is: Phenyltrimethoxysilane was used as raw material, and the hydrolysis-condensation method was adopted. The hydrolysis-condensation reaction of phenyltrimethoxysilane was catalyzed by sodium hydroxide. 3-dimethylaminopropyl (dimethoxy)methylsilane was used as a capping agent. Di(tertiary amino) octaphenyl cage-type polysilsesquioxane monomer was synthesized by the vertex-capping method under the catalysis of triethylamine. By utilizing the nucleophilic substitution reaction mechanism, the tertiary amine functional group of the nucleophilic reagent di(tertiary amino) octaphenyl cage-type polysilsesquioxane monomer undergoes a quaternization reaction with the chlorine functional group of epichlorohydrin to generate a di(epoxy) cage-type organosilicon quaternary ammonium salt crosslinking agent.

4. The method for preparing a nine-layer co-extruded high temperature resistant film containing polyethylene and nylon according to claim 1, It is characterized in that The preparation method of the nine-layer co-extruded high temperature resistant film containing polyethylene and nylon materials is as follows: Step 1: Design the film structure of the nine-layer co-extruded high temperature resistant film and determine the raw materials and dosage of each film layer, as follows: The first polyethylene layer: the raw material is low-density polyethylene resin, the dosage is 5~15wt%; Second polyethylene layer: the raw material is high-density polyethylene resin, the dosage is 5~15wt%; The third polyethylene layer: the raw material is low-density polyethylene resin, the dosage is 5~15wt%; The first bonding layer: the raw material is maleic anhydride grafted polyethylene resin, the dosage is 3~8wt%; Nylon layer: the raw material is high temperature resistant nylon composite material, the dosage is 20~40wt%; Second bonding layer: the raw material is maleic anhydride grafted polyethylene resin, the dosage is 3~8wt%; The fourth polyethylene layer: the raw material is low-density polyethylene resin, the dosage is 5~15wt%; The fifth polyethylene layer: the raw material is high-density polyethylene resin, the dosage is 5~15wt%; The sixth polyethylene layer: the raw material is low-density polyethylene resin, the dosage is 5~15wt%; Step 2: Using a nine-layer co-extrusion film blowing unit, and controlling the blowing ratio at 2.5-2.9, a nine-layer co-extruded high temperature resistant film is prepared.

5. A method for preparing a nine-layer co-extruded high temperature resistant film containing polyethylene and nylon materials according to claim 4, It is characterized in that The plasticizing extrusion process parameters of the nylon layer are as follows: the temperatures of zones 1-3 are 240-260° C., 270-290° C., and 310-330° C., respectively; the flow channel temperature is 310-320° C.; and the rotation speed is 50-70 r / min.

6. A nine-layer co-extruded high temperature resistant film containing polyethylene and nylon prepared by the method according to any one of claims 1 to 5, It is characterized in that The thickness of the nine-layer co-extruded high temperature resistant film is 50-150 μm.

7. A nine-layer co-extruded high temperature resistant film containing polyethylene and nylon according to claim 6, It is characterized in that The heat deformation temperature of the nine-layer co-extruded high temperature resistant film is greater than 200°C.

8. Application of a nine-layer co-extruded high temperature resistant film containing polyethylene and nylon prepared by the method according to any one of claims 1 to 5, It is characterized in that The nine-layer co-extruded high-temperature resistant film can be used as a diaphragm in a hot diaphragm forming process in a carbon fiber autoclave forming process.